Pengaruh kepribadian, letak kendali perilaku, dan motivasi terhadap otonomi remaja memilih perguruan tinggi - Hasnin, Hanrezi Dhania (Konsorsium Psikologi Ilmiah Nusantara, 2015)
This study examines the impacts of personality trait, locus of control and motivation to the adolescent’s autonomy on choosing university. Respondents are 222 adolescents, between 16 to 20 years of age, have graduated from high school, have decided to continue study into college or university and are preparing for university’s entry examinations. The data are collected using the Big Five Personality Traits questionnaire, Levenson’s IPC Locus of Control questionnaire, Motivation, and Behavioral Autonomy questionnaire that are adapted for the purposes of this study. Results from multiple regression analyses show that some of dimensions in personality traits, locus of control and motivation affect adolescent’s autonomy from father, mother or both on choosing higher education institutions. Moreover, they show that (1) chance and encouragement from others had negative impacts to adolescent’s autonomy from father’s influence for choosing higher education institutions, while on the career motivation it has positive impact. (2) there is no significant impact of all dimensions in personality trait, locus of control, and motivation to adolescent’s autonomy form mother’s influence. (3) chance has significant negative impact to adolescent’s autonomy from parent’s influence.